Advances in Cancer Therapy - Gali-Muhtasib, Hala; Gali-Muhtasib, Hala (InTechOpen, 2011)
The book "Advances in Cancer Therapy" is a new addition to the Intech collection of books and aims at providing scientists and clinicians with a comprehensive overview of the state of current knowledge and latest research findings in the area of cancer therapy. For this purpose research articles, clinical investigations and review papers that are thought to improve the readers' understanding of cancer therapy developments and/or to keep them up to date with the most recent advances in this field have been included in this book. With cancer being one of the most serious diseases of our times, I am confident that this book will meet the patients', physicians' and researchers' needs.
eng
Keywords: Cancer -- Treatment; Cancer -- Traitement; Cancer -- Treatment; Mathematics and science; Mathematics and Science; Science: general issues; Science: general issues; cancer therapy